Lvr, a Signaling System That Controls Global Gene Regulation and Virulence in Pathogenic Leptospira - Adhikarla, Haritha; Wunder, Elsio A.; Mechaly, Ariel E.; Mehta, Sameet; Wang, Zheng; Santos, Luciane; Bisht, Vimla; Diggle, Peter; Murray, Gerald; Adler, Ben; Lopez, Francesc; Townsend, Jeffrey P.; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Leptospirosis is an emerging zoonotic disease with more than 1 million cases annually. Currently there is lack of evidence for signaling pathways involved during the infection process of Leptospira. In our comprehensive genomic analysis of 20 Leptospira spp. we identified seven pathogen specific Two-Component System (TCS) proteins. Disruption of two these TCS genes in pathogenic Leptospira strain resulted in loss of virulence in a hamster model of leptospirosis. Corresponding genes lvrA and lvrB (leptospira virulence regulator) are juxtaposed in an operon and are predicted to encode a hybrid histidine kinase and a hybrid response regulator, respectively. Transcriptome analysis of lvr mutant strains with disruption of one (lvrB) or both genes (lvrA/B) revealed global transcriptional regulation of 850 differentially expressed genes. Phosphotransfer assays demonstrated that LvrA phosphorylates LvrB and predicted further signaling downstream to one or more DNA-binding response regulators, suggesting that it is a branched pathway. Phylogenetic analyses indicated that lvrA and lvrB evolved independently within different ecological lineages in Leptospira via gene duplication. This study uncovers a novel-signaling pathway that regulates virulence in pathogenic Leptospira (Lvr), providing a framework to understand the molecular bases of regulation in this life-threatening bacterium.